HOW DOES ZAKAT EMPOWER SOCIETY? A CASE STUDY OF THE KHAIRPUR DISTRICT, PAKISTAN - Safiullah Junejo; Saba Anwar (Jurnal Sosiologi Reflektif, 2023)
Poverty is a worldwide issue of concern to the international community, including Pakistan. Khairpur is a rural region in Pakistan where a significant proportion of the population lives below the poverty threshold. This research aims to describe the practice of zakat and its implications for the residents of the Khairpur district in Pakistan, using qualitative research techniques. The methods employed to collect data in this study involved conducting interviews with Khairpur residents, observations, and reviewing relevant literature. The findings indicated that in Khairpur, the local community perceives the practice of zakat as a means of providing socio-economic security for the elderly by allocating zakat funds to healthcare facilities. Donating Zakat to educational institutions can also provide assistance to economically vulnerable groups of children. Zakat initiatives can aid women's groups in funding their wedding expenses and dowries. Nevertheless, this research also exposed that the transparency of zakat management has been inadequate and requires further improvement to ensure that a larger portion of the Khairpur population can reap the benefits of zakat.Problem global kemiskinan telah lama menjadi perhatian masyarakat dunia, termasuk di Pakistan. Khairpur adalah salah satu daerah pedesaan Pakistan yang memiliki banyak segmen masyarakat yang hidup di bawah garis kemiskinan. Penelitian ini bermaksud untuk menjelaskan praktik zakat dan refleksinya bagi masyarakat di distrik Khairpur Pakistan melalui metode kualitatif.  Teknik pengumpulan data dilakukan melalui sejumlah wawancara dengan penduduk Khairpur, observasi, dan telaah pustaka. Hasil penelitian menunjukkan bahwa praktik zakat di Khairpur telah dianggap oleh masyarakat setempat dapat memberikan jaminan sosial ekonomi untuk orang lanjut usia melalui zakat yang dialokasi ke dalam fasilitas kesehatan. Zakat yang dialokasikan ke dalam fasilitas pendidikan juga mampu membantu kelompok anak-anak yang memiliki kerentanan ekonomi. Sedangkan bagi bagi kelompok perempuan, program zakat dapat membantu mereka dalam pembiayaan mahar maupun upacara pernikahan. Meski demikian, pada sisi lain, penelitian ini juga mengungkapkan bahwa praktik pengelolaan zakat belum transparan dan masih perlu ditingkatkan lagi jumlahnya agar semakin banyak segmen penduduk Khairpur yang merasakan manfaat zakat tersebut.